App Users Unwittingly in the Spotlight: A Model of Privacy Protection in Mobile Apps. Issue 3 (4th July 2018) - Wottrich, Verena M.; van Reijmersdal, Eva A.; Smit, Edith G.
Abstract : Mobile apps are increasingly jeopardizing app users' online privacy by collecting, storing, and sharing personal data disclosed via apps. However, little is known about mobile app users' current privacy protection behavior and the factors that motivate it. Drawing on Roger's Protection Motivation Theory (PMT), this study develops and tests the App Privacy Protection Model among 1, 593 Western European app users. The results demonstrate that, on the one hand, increased levels of perceived self‐efficacy, vulnerability, and privacy concern enhance mobile app users' motivation to engage in risk‐reducing behavior, while on the other hand, higher levels of knowledge of the data collection practices of mobile apps, app attitude, and perceived response costs diminish it. Being the first study that applies PMT in the mobile app context, this study offers several important implications regarding privacy protection in mobile apps.